PENGARUH KOMPETENSI GURU AGAMA KATOLIK TERHADAP PRESTASI BELAJAR SISWA- SISWI DI SMP NEGERI 2 KUPANG - Siono, Yeremias; Taek, Emilia Dolorosa (Pastoralia Jurnal Penelitian Dosen, 2020)
The study is entitled The Effect Of Competency Of Catholic Religion Teachers On Student Learning Achievements In Kupang 2 State Smp. The reason the authors chose this title was because based on the writer's observations while carrying out field experience in Kupang State Middle School 2, the authors saw the lack of activeness of students in attending lessons, it was caused due to lack of infrastructure such as classrooms to carry out learning activities and most students also thought religious studies are lessons that are young or not difficult. Because it is called for a Catholic teacher who has competence in teaching. The results of the study showed that based on descriptive statistical analysis the achievement of Catholic teacher teacher competency indicators on student achievement in Kupang 2 Public Middle School was 33.10% or in the poor category, while the achievement of student learning achievement indicators was 33.8% at categorically not good means that Catholic teachers do not show the ability in teaching and learning activities. Based on the results of the partial test (t) it is known that the calculated value 1.369 with a significant level of 0.000 this significant value is smaller than the alpha set which is 0.05, the decision is to reject the null hypothesis (Ho) and accept the alternative hypothesis (Ha), meaning variableCatholic teacher competence (X) has a significant effect on student learning achievement (Y) in Kupang State Middle School 2.